2001
DOI: 10.1128/aem.67.6.2436-2444.2001
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of a Psychrophilic, Calcium-Induced, Growth-Phase-Dependent Metalloprotease from the Fish Pathogen Flavobacterium psychrophilum

Abstract: Flavobacterium psychrophilum is a fish pathogen that commonly affects salmonids. This bacterium produced an extracellular protease with an estimated molecular mass of 55 kDa. This enzyme, designated Fpp1 (F. psychrophilum protease 1), was purified to electrophoretic homogeneity from the culture supernatant by using ammonium sulfate precipitation, ion-exchange chromatography, hydrophobic chromatography, and size exclusion chromatography. On the basis of its biochemical characteristics, Fpp1 can be included in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(95 citation statements)
references
References 58 publications
5
88
1
1
Order By: Relevance
“…In the present study, a difference in ECP profiles between the smooth and rough cells was observed, as the P13 rough variant and the wild type isolate showed 5 intensely stained bands compared to no bands or weakly stained bands in the P13 smooth variant. Two of these protein bands had approximate molecular weights of 55 and 65 kDa and may be the 55 kDa Fpp1 and the 62 kDa Fpp2 metalloproteases previously found in F. psychrophilum (Secades et al 2001(Secades et al , 2003, indicating that the P13 rough cells could have a higher ability to hydrolyze a range of matrix and muscle proteins compared to the P13 smooth cells. The 55 and 65 kDa protein bands were not evident, however, in the ECP profiles of the P6 isolates, which could in part be due to the age differences between the isolates.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, a difference in ECP profiles between the smooth and rough cells was observed, as the P13 rough variant and the wild type isolate showed 5 intensely stained bands compared to no bands or weakly stained bands in the P13 smooth variant. Two of these protein bands had approximate molecular weights of 55 and 65 kDa and may be the 55 kDa Fpp1 and the 62 kDa Fpp2 metalloproteases previously found in F. psychrophilum (Secades et al 2001(Secades et al , 2003, indicating that the P13 rough cells could have a higher ability to hydrolyze a range of matrix and muscle proteins compared to the P13 smooth cells. The 55 and 65 kDa protein bands were not evident, however, in the ECP profiles of the P6 isolates, which could in part be due to the age differences between the isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the psychrotrophic properties of F. psychophilum enzymes: only the metalloproteases Fpp1 and Fpp2 were biochemically characterized and reported to display a psychrophilic and thermolabile behavior 13,14 . The psychrotolerant Flavobacterium frigidimaris produces seven NAD(P) + -dependent dehydrogenases 44 ; four of them were psychrophilic and thermolabile, whereas the other three were unexpectedly thermophilic and thermostable.…”
Section: A R T I C L E Smentioning
confidence: 99%
“…The two metalloproteases Fpp1 (ref. 13) and Fpp2 (ref. 14) hydrolyze a broad range of substrates, including basic elements of muscular tissues.…”
Section: Toxinsmentioning
confidence: 99%
“…13) The poor recovery of the plant enzymes is further aggravated by the fact that most of them are cellularly bound. 14,15) Because of these inherent problems, researchers working on plant enzymes have incorporated various reducing agents, 16,17) activators, 18,19) and detergents 10,20) in order to improve the extraction and the stability of the enzymes, but the use of such reagents must to be optimized due to economic and technological considerations.…”
mentioning
confidence: 99%